2021
DOI: 10.3390/ph14030213
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of Some Natural Product Isolates as SARS-COV-2 Main Protease Inhibitors via In Vitro Cell Free and Cell-Based Antiviral Assessments and Molecular Modeling Approaches

Abstract: The emergence of the SARS-CoV-2 pandemic has prompted scientists to search for an efficient antiviral medicine to overcome the rapid spread and the marked increase in the number of patients worldwide. In this regard natural products could be a potential source of substances active against coronavirus infections. A systematic computer-aided virtual screening approach was carried out using commercially available natural products found on the Zinc Database in addition to an in-house compound library to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 50 publications
3
43
1
1
Order By: Relevance
“…Among compounds, myrcetin (flavonol), naringenin (flavonone) and epigallocatechin (flavan-3-ol), vitexin (flavone) and diarylheptanoid dimethylcurcumin (curcuminoid) were the most active. Focusing on naringenin, the obtained result agrees with other in vitro studies that reported that, in fact, this compound can interact with M pro , showing an inhibitory IC 50 value of 92 nM [ 89 ]. This compound is very abundant in orange, grapefruits and derivative juices, which in turn, present considerable amounts of vitamins C and D, and whose abilities to reduce the severity of symptoms caused by flu states are known [ 62 , 90 , 91 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19supporting
confidence: 89%
“…Among compounds, myrcetin (flavonol), naringenin (flavonone) and epigallocatechin (flavan-3-ol), vitexin (flavone) and diarylheptanoid dimethylcurcumin (curcuminoid) were the most active. Focusing on naringenin, the obtained result agrees with other in vitro studies that reported that, in fact, this compound can interact with M pro , showing an inhibitory IC 50 value of 92 nM [ 89 ]. This compound is very abundant in orange, grapefruits and derivative juices, which in turn, present considerable amounts of vitamins C and D, and whose abilities to reduce the severity of symptoms caused by flu states are known [ 62 , 90 , 91 ].…”
Section: Uptake Of Phenolic Compounds In Dietary Supplements In Covid-19supporting
confidence: 89%
“…Results showed that the extract inhibited HSV-1 replication by blocking much of viral gene expression, which almost halved at a concentration of 10 µg/mL. The outcomes on the replication are in accordance with literature [67][68][69][70][71], demonstrating that the leaf extract had a virucidal action and could be used as a prophylactic treatment for herpetic infections. Anti-SARS-CoV-2 activity of V. vinifera leaf extract was also investigated through the spike protein (S) gene expression (Figure 8).…”
Section: Cytotoxicity Evaluationsupporting
confidence: 87%
“…Recently, a number of other natural products have shown interesting inhibitory activity against SARS CoV-2 M pro catalytic activity, particularly flavonoids [ 14 , 15 , 16 ]. For example, baicalein has exhibited potent micromolar inhibition (IC 50 = 0.94 µM), and its crystal structure with M pro indicated that its main molecular interactions were with GLY-143 and GLU-166 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%